Patients with high-risk DLBCL benefit from dose-dense immunochemotherapy combined with early systemic CNS prophylaxis - Sirpa Leppä; Judit Jørgensen; Anne Tierens; Leo Meriranta; Ingunn Østlie; Peter de Nully Brown; Unn-Merete Fagerli; Thomas Stauffer Larsen; Susanna Mannisto; Lars Munksgaard; Martin Maisenhölder; Kaija Vasala; et al. (AMER SOC HEMATOLOGY, 2022)
Survival of patients with high-risk diffuse large B-cell lymphoma (DLBCL) is suboptimal, and the risk of central nervous system (CNS) progression is relatively high. We conducted a phase 2 trial in 139 patients aged 18 to 64 years who had primary DLBCL with an age-adjusted International Prognostic Index (aaIPI) score of 2 to 3 or site-specific risk factors for CNS recurrence. The goal was to assess whether a dose-dense immunochemotherapy with early systemic CNS prophylaxis improves the outcome and reduces the incidence of CNS events. Treatment consisted of 2 courses of high-dose methotrexate in combination with biweekly rituximab (R), cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP-14), followed by 4 courses of R-CHOP-14 with etoposide (R-CHOEP) and 1 course of high-dose cytarabine with R. In addition, liposomal cytarabine was administered intrathecally at courses 1, 3, and 5. Coprimary endpoints were failure-free survival and CNS progression rates. Thirty-six (26%) patients experienced treatment failure. Progression occurred in 23 (16%) patients, including three (2.2%) CNS events. At 5 years of median follow-up, failure-free survival, overall survival, and CNS progression rates were 74%, 83%, and 2.3%, respectively. Treatment reduced the risk of progression compared with our previous trial, in which systemic CNS prophylaxis was given after 6 courses of biweekly R-CHOEP (hazard ratio, 0.49; 95% CI, 0.31-0.77; P=.002) and overcame the adverse impact of an aaIPI score of 3 on survival. In addition, outcome of the patients with BCL2/MYC double-hit lymphomas was comparable to the patients without the rearrangements. The results are encouraging, with a low toxic death rate, low number of CNS events, and favorable survival rates.